Antioxidant active packaging based on papaya edible films incorporated with Moringa oleifera and ascorbic acid for food preservation. (June 2020) - Rodríguez, Gisella M.; Sibaja, Juan C.; Espitia, Paula J.P.; Otoni, Caio G.
Abstract: Edible films made from papaya ( Carica papaya L.) with antioxidant activity for food preservation were developed. First, film drying conditions (solvent casting at room temperature, dehydrator, and oven) were studied considering water activity, color, thickness, and sensory evaluation. The optimum drying condition was selected for subsequent steps, wherein Moringa leaf extract and ascorbic acid were incorporated into the films either individually or simultaneously at 6 wt% each. The films were characterized regarding antioxidant activity, physicochemical properties (water activity, thickness, color, pH, and content of total soluble solids), mechanical properties, bromatology, and sensory acceptance. Moreover, the performance of the films in contact with minimally processed pears was assessed by means of sensory evaluation and physicochemical properties of this food matrix. Films dried by different methods presented no significant difference as for the evaluated parameters. In this sense, the dehydrator was selected for further film-forming procedures because of the reasonable drying time (4 h) as well as suitable preservation of the in natura physicochemical and sensory properties. Films incorporated with ascorbic acid and those with the mixture of moringa and ascorbic acid presented no significant difference, with both treatments having the highest antioxidant activity. All studied physicochemical and mechanical properties had significant difference among the tested treatments, except for pH. Finally, the incorporation of both bioactive compounds showed an influence on the shelf-life stability of minimally processed pears, with the edible film incorporated with ascorbic acid presenting positive influence on the sensory acceptance of such a food matrix. Graphical abstract: Image 1 Highlights: Papaya edible films incorporated with ascorbic acid and moringa were developed. Drying conditions of developed papaya edible films were studied. Antioxidant activity in vitro of developed papaya edible films were tested. Effect of edible films was assessed on the preservation of minimally processed pear.